2021
DOI: 10.4012/dmj.2020-272
|View full text |Cite|
|
Sign up to set email alerts
|

Back to the multi-step adhesive system: A next-generation two-step system with hydrophobic bonding agent improves bonding effectiveness

Abstract: This study evaluated the bonding effectiveness of a newly developed two-step hydrophobic bonding material. Three groups using different bonding systems were compared: BZF group, using the new bonding system (BZF-29; GC, Tokyo, Japan); GPB group, using a one-step bonding system (G-Premio Bond; GC); and SE2 group, using a two-step bonding system (CLEARFIL SE Bond 2; Kuraray Noritake Dental, Tokyo, Japan). Microtensile bond strength (µTBS) was measured after storage in water for 24 h, 3 months and 6 months (n=25/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Additionally, the stress distribution might be different because of the different mechanical properties of each adhesive layer. In particular, the HEMA-, solvent-, and functional monomer-free bonding agent in GU is thought to create a hydrophobic adhesive layer, which might have higher mechanical properties than those formed in the other adhesives [15,16]. This might explain why GU was the only adhesive to show a significantly higher SBS in the ER mode than that in the SE mode at TC 10,000 in Group III.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the stress distribution might be different because of the different mechanical properties of each adhesive layer. In particular, the HEMA-, solvent-, and functional monomer-free bonding agent in GU is thought to create a hydrophobic adhesive layer, which might have higher mechanical properties than those formed in the other adhesives [15,16]. This might explain why GU was the only adhesive to show a significantly higher SBS in the ER mode than that in the SE mode at TC 10,000 in Group III.…”
Section: Discussionmentioning
confidence: 99%
“…A recently introduced two-step adhesive system comprises a 2-hydroxyethyl methacrylate (HEMA)-free universal adhesive-derived primer and a hydrophobic bonding agent without any solvents or functional monomers. This adhesive system showed superior bond durability under thermal stress and long-term water storage when compared with conventional two-step self-etch adhesives, regardless of the tooth substrate or etching mode used [15]. Moreover, Tamura et al [16] showed that the enamel and dentin bond durability achieved under fatigue stress by the new two-step adhesive system was equivalent to that attained by a gold standard two-step self-etch adhesive, Clearfil SE Bond.…”
Section: Introductionmentioning
confidence: 99%
“…Three different types of two-step adhesive systems were used in the present study. G2-Bond Universal is the most recent two-step adhesive system, and utilizes universal adhesive technologies for its primer along with a highly hydrophobic bonding agent [4][5][6]. Theoretically, G2-Bond Universal can be used in the etch-and-rinse and/or self-etch mode with both enamel and dentin because the primer is similar in composition to universal adhesives [15].…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributed to the characteristics of the primer and the bonding agent. G2-Bond Universal is a HEMA-free adhesive system, and the bonding agent does not contain any functional monomers or solvents, unlike Clearfil SE Bond 2 and OptiBond eXTRa [4][5][6]. HEMA is thought to be susceptible to hydrolysis, and the functional monomers in the bonding agent might facilitate hydrolysis owing to the hydrophilic moieties [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation